2008
DOI: 10.1073/pnas.0803998105
|View full text |Cite
|
Sign up to set email alerts
|

The Parkinson's disease genes pink1 and parkin promote mitochondrial fission and/or inhibit fusion in Drosophila

Abstract: Mutations in PTEN-induced kinase 1 (pink1) or parkin cause autosomal-recessive and some sporadic forms of Parkinson's disease. pink1 acts upstream of parkin in a common genetic pathway to regulate mitochondrial integrity in Drosophila. Mitochondrial morphology is maintained by a dynamic balance between the opposing actions of mitochondrial fusion, controlled by Mitofusin (mfn) and Optic atrophy 1 (opa1), and mitochondrial fission, controlled by drp1. Here, we explore interactions between pink1/parkin and the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
572
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 636 publications
(615 citation statements)
references
References 39 publications
(63 reference statements)
40
572
2
1
Order By: Relevance
“…Light microscopic observations of fly spermatids reveal that nebenkerns are swollen and fail to properly divide in PINK1 and parkin mutants. These observations indicate that PINK1 and Parkin control mitochondrial fusion -fission processes (Deng et al, 2008).…”
Section: Parkin Remodels Mitochondria By Ubquitinating Its Mitochondrmentioning
confidence: 86%
See 1 more Smart Citation
“…Light microscopic observations of fly spermatids reveal that nebenkerns are swollen and fail to properly divide in PINK1 and parkin mutants. These observations indicate that PINK1 and Parkin control mitochondrial fusion -fission processes (Deng et al, 2008).…”
Section: Parkin Remodels Mitochondria By Ubquitinating Its Mitochondrmentioning
confidence: 86%
“…Moreover, further genetic analyses using mitochondrial fusionfission regulators demonstrated that PINK1 and parkin mutant phenotypes are successfully rescued by the overexpression of Drp1, a dynamin-related GTPase that promotes mitochondrial fission, or the downeregulation of Opa1 or Marf, which are other dynamin-related GTPases that induce mitochondrial fusion (Deng et al, 2008;Park et al, 2009;Poole et al, 2008;Yang et al, 2008). These findings suggest that PINK1 and Parkin balance mitochondrial dynamics by promoting mitochondrial fission to properly maintain mitochondrial function.…”
Section: Parkin Remodels Mitochondria By Ubquitinating Its Mitochondrmentioning
confidence: 88%
“…Therefore, defective mitophagy due to a lack of parkin recruitment to impaired mitochondria by PINK1 causes the accumulation of dysfunctional mitochondria and a subsequent enhanced ROS levels and proapoptotic proteins [257]. In addition, overexpression of PINK1 promotes mitochondrial fission, while inhibition of the protein causes an excessive fusion [258,259]. Fibroblasts from PD patients carrying homozygous PINK1 mutations had truncated mitochondria networks compared to control fibroblasts, when cultured in medium with low glucose, or in the presence of galactose to favor mitochondrial energy metabolism over glycolysis [243,260].…”
Section: Ptenǧinduced Putative Kinase 1 (Pink1)mentioning
confidence: 99%
“…Therefore, defective mitophagy due to a lack of parkin recruitment to impaired mitochondria by PINK1 causes the accumulation of dysfunctional mitochondria and subsequent enhanced ROS levels and proapoptotic proteins [257]. In addition, overexpression of PINK1 promotes mitochondrial fission, whereas inhibition of the protein causes excessive fusion [258,259]. Fibroblasts from PD patients carrying homozygous PINK1 mutations had truncated mitochondria networks compared to control fibroblasts, when cultured in medium with low glucose or in the presence of galactose to favor mitochondrial energy metabolism over glycolysis [243,260].…”
Section: Pink1 and Parkinmentioning
confidence: 99%